Treating Stress With VR. (8th May 2020) - Naylor, Matthew
Abstract: The paper 'Augmented Experiences: Investigating the Feasibility of Virtual Reality as Part of a Workplace Wellbeing Intervention' by Matthew Naylor et al, published in Interacting with Computers, Volume 31, Issue 5, September 2019, explores the immersive power of VR in psychological wellbeing.